A THEMATIC ANALYSIS OF CONSUMERS’ SELF-REPORTED THOUGHTS REGARDING BRAND LOYALTY AND COMMUNICATION DURING A HEALTH CRISIS - Strous, Samuel (The IIE, 2022)
Literature on strategic brand communication during crises emphasises the importance of protecting consumer-brand relationships. However, little research exists on consumers’ views on how brand communications may affect consumer-brand relationships and brand loyalty during health crises. This is important to glean particularly during the current coronavirus pandemic. A convenience sample of eight consumers were interviewed as to how they thought brand communication may either strengthen or weaken their loyalty to a brand during a crisis that threatens or has affected their health. Thematic analysis of the interviews yielded several themes. Consumers preferred (a) direct, transparent, accurate information focussed on safety and trust; (b) competent, trustworthy sources; (c) consistent, coherent communication across multiple platforms; (d) empathic, compassionate communication; (e) accountability; (f) well-timed, proactive, swift and efficient communication; and (g) once safety has been dealt with, messages regarding value and utility. The participants perceive loyalty-weakening brand communication as (a) imprecise with poor explanatory power and solutions; (b) lacking credibility; (c) disparate; (d) insensitive; (e) lacking in integrity; (f) inefficient, delayed, or rushed; and (f) communicating little information regarding value and utility. These findings have practical implications for brand managers.
Keywords: Pandemic; Brand awareness; Consumer behaviour; Brand trust